Si-C coupling reaction of polychloromethanes with HSiCl(3) in the presence of Bu(4)PCl: Convenient synthetic method for bis(chlorosilyl)methanes - Jung, Dong Euy; Kang, Seung-Hyun; Han, Joon Soo; Lim, Weon Cheol; Park, Young-ae W.; Yoo, Bok Ryul (ELSEVIER SCIENCE SA, 2007)
Coupling reaction of polychloromethanes CH(4-n)Cl(n) (n = 2-4) with HSiCl(3) in the presence of tetrabutylphosphonium chloride (Bu(4)PCl) as a catalyst occurred at temperatures ranging from 30 degrees C to 150 degrees C. The reactivity of polychloromethanes increases as the number of chlorine-substituents on the carbon increases. In the reactions Of CCl(4) with HSiCl(3), a variety of coupling products such as bis(chlorosilyl)methanes CH(2)(SiCl(3))(SiXCl(2)) [X = Cl (1a), H (1b)], (chlorosilyl)trichloromthanes Cl(3)CSiXCl(2) [X = Cl (2a), H (2b)], and (chlorosilyl)dichloromthanes Cl(2)HCSiXCl(2) [X = Cl (3a), H (3b)] were obtained along with reductive dechlorination products such as CHCl(3) and CH(2)Cl(2) depending on the reaction temperature. In the reaction Of CCl(4), 2a is formed at the initial stage of the coupling reaction and converted to give CHCl(3) at low temperature of 30 degrees C, to give la, 3a, and CHCl(3) at 60 degrees C, and to afford la as major product and CH(2)Cl(2) in competition above 100 degrees C. Si-H bond containing silylmethanes can be formed by the H-Cl exchange reaction with HSiCl(3). Reaction of CHCl(3) with HSiCl(3) took placed at 80 degrees C to give three compounds la, 3a, and CH(2)Cl(2), and finally 3a was converted to give la and CH2Cl2 at longer reaction time. While the condition for the reaction of CH(2)O(2) with HSiCl(3) required a much higher temperature of 150 degrees C. Under the optimized conditions for synthesizing bis(chlorosilyl)methanes la,b, a mixture of la and 1b were obtained as major products in 65% (1a:1b = 64: 1) and 47% (42:5) yields from the reaction of CCl(4) and CHC13 at 100 'C for 8 h, respectively, and in 41% (34:7) yield from that of CH(2)Cl(2) at 170 degrees C for 12 h. In the Si-C coupling reaction of polychloromethanes with HSiCl(3), it seems likely that a trichlorosilyl anion generated from the reaction of HSiCl(3) with Bu(4)Pcl is an important key intermediate. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: AMINE COMBINATIONS; ALKYL-HALIDES; TRICHLOROSILANE; CHLORIDE; SILYLATION; CHEMISTRY; SILICON